Chromosome-Scale Genome Assembly of the Hexaploid Taiwanese Goosefoot "Djulis" (Chenopodium formosanum) - Jarvis, David E; Sproul, John S; Navarro-Domínguez, Beatriz; Krak, Karol; Jaggi, Kate; Huang, Yung-Fen; Huang, Tzu-Yun; Lin, Tzu Che; Jellen, Eric N; Maughan, Peter J (Genome biology and evolution, 2022)
Djulis (Chenopodium formosanum Koidz.) is a crop grown since antiquity in Taiwan. It is a BCD-genome hexaploid (2n = 6x = 54) domesticated form of lambsquarters (C. album L.) and a relative of the allotetraploid (AABB) C. quinoa. As with quinoa, djulis seed contains a complete protein profile and many nutritionally important vitamins and minerals. While still sold locally in Taiwanese markets, its traditional culinary uses are being lost as diets of younger generations change. Moreover, indigenous Taiwanese peoples who have long safeguarded djulis are losing their traditional farmlands. We used PacBio sequencing and Hi-C-based scaffolding to produce a chromosome-scale, reference-quality assembly of djulis. The final genome assembly spans 1.63 Gb in 798 scaffolds, with 97.8% of the sequence contained in 27 scaffolds representing the nine haploid chromosomes of each sub-genome of the species. Benchmarking of universal, single-copy orthologs indicated that 98.5% of the conserved orthologous genes for Viridiplantae are complete within the assembled genome, with 92.9% duplicated, as expected for a polyploid. A total of 67.8% of the assembly is repetitive, with the most common repeat being Gypsy long terminal repeat retrotransposons, which had significantly expanded in the B sub-genome. Gene annotation using Iso-Seq data from multiple tissues identified 75,056 putative gene models. Comparisons to quinoa showed strong patterns of synteny which allowed for the identification of homoeologous chromosomes, and sub-genome-specific sequences were used to assign homoeologs to each sub-genome. These results represent the first hexaploid genome assembly and the first assemblies of the C and D genomes of the Chenopodioideae subfamily.
Keywords: polyploidie; Chenopodium; long-read sequencing; retrotransposon; Chromosomes, Plant; syntenie; Polyploidy; LTR; chromosome-scale; Gypsy; Synteny; genom rostlinný; chromozomy rostlin; polyploid evolution; Genome, Plant